Dynamic behavior of FG-TPMS sandwich plates on a Pasternak viscoelastic foundation under moving loads using Moving Element Method - Do, Thành Huế; Chu , Thái Nam; Nguyen, Huy Vững (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study investigates the dynamic response of sandwich plates with a functionally graded triply periodic minimal surface (FG-TPMS) core, supported by a viscoelastic foundation, under the influence of moving loads. Inspired by natural biological structures, the FG-TPMS core provides a unique artificial design known for its superior load-bearing capabilities compared to conventional frameworks. Due to its exceptional strength-to-weight ratio, the TPMS structure delivers a lightweight yet robust solution, optimizing material usage while ensuring high structural efficiency. The Moving Element Method (MEM) is employed for dynamic analysis, offering notable advantages over traditional techniques in handling moving load problems. Additionally, MEM proves effective in addressing boundary condition sensitivity issues in TPMS-based plates. To gain deeper insight into the behavior of FG-TPMS sandwich plates under dynamic loads, key parameters - including the minimum relative density, the isotropic layer thickness, and the TPMS core thickness - will be comprehensively examined.